Fluoride content and pH levels of commercially available iced tea powder mixes in Metro Manila, Philippines a cross-sectional study - Pechayco, Roan S.; Plandez, Joanne D.; Meneses, Michelle Marie Z. (Co-author).; Mendoza, Michael Antonio F.(Co-author & Adviser).
Tea is known to be a source of fluoride which increases the resistance of tooth against dental caries. With the advent of producing instant products, iced tea powder mixes were formulated. However, after processing, the fluoride content of these products is unknown. For children below 8 years old, too much fluoride can cause dental fluorosis characterized by enamel mottling. For adults, there is a concern that skeletal fluorosis might result when excessive volumes were consumed. Also with added ingredients such as lemon flavor, citric acid and vitamins such as ascorbic acid, it is not known whether these products can cause dental erosion. Objectives: To determine the presence of fluoride, and if present, the fluoride content in parts per million (ppm), and pH levels of commercially available iced tea powder mixes; and to formally forward the results to FDA for possible policy formulation and fluoride regulation in beverages. Methods: The study included seven brands of iced tea powder mixes which were commonly available in Metro Manila. Ion selective electrode method and pH testing machine were used to determine the amount of fluoride in parts per million and pH levels, respectively. Results: Fluoride content measured were <2.00 ppm in six brands and >2.00 ppm in one brand, which exceeded the fluoride limit for bottled drinking water and RENI values for Filipinos. The pH ranged from 3.76 to 2.73. Conclusions: All of the seven commercially available iced tea powder mixes contain fluoride and are found to be acidic enough to cause dental erosion if these refreshment were excessively consumed for a prolonged period of time.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Fluorides